Cervical cancer mortality trends in Brazil, 1981-2006 Evolução da mortalidade por câncer do colo do útero no Brasil, 1981-2006 - Gulnar Azevedo e Silva; Vania Reis Girianelli; Carmen Justina Gamarra; Maria Teresa Bustamante-Teixeira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
The aim of this study was to describe cervical cancer mortality trends in Brazil for the period 1981-2006. Cervical cancer mortality was corrected on the basis of proportional redistribution of the deaths from "malignant neoplasm of uterus, part unspecified". Time trends were evaluated by means of simple linear regression. After correction, cervical cancer ranked second among the leading causes of death from cancer in the female population up to 2005, with a downward trend for the country as a whole, a decline in the State capitals, and a stable trend in the municipalities in the interior. A downward trend was confirmed in the State capitals in all geographic regions of the country. In the municipalities in the interior, there was an increase in the North and Northeast regions, a decline in the Southeast and South, and a stable trend in the Central-West. Although uneven, the decline began to take consistent shape in the country. Even better results could be achieved by investing in the expansion of screening coverage, especially among the populations at greatest risk. Este estudo objetivou descrever a evolução da mortalidade por câncer do colo do útero no Brasil, entre 1981-2006. Foi efetuada correção da mortalidade por esse câncer com base na redistribuição proporcional dos óbitos por câncer do útero, "porção não especificada". A tendência temporal foi avaliada por meio de regressão linear simples. Após correção, as taxas de mortalidade por câncer do colo do útero passaram a ocupar o segundo lugar entre os principais cânceres na população feminina até 2005, com tendência decrescente para o país como um todo, queda nas capitais e estabilidade nos municípios do interior. Confirmou-se tendência decrescente nas capitais em todas as regiões do país. Já nos municípios do interior, houve aumento nas regiões Norte e Nordeste, declínio nas regiões Sudeste e Sul e estabilidade no Centro-oeste. A queda observada, mesmo que ainda de forma desigual, começa a se esboçar consistentemente no país. E poderia alcançar resultados ainda melhores com investimento no aumento de cobertura do rastreamento, especialmente entre as populações de maior risco.